Neuropterida (Insecta: Megaloptera, Raphidioptera, Neuroptera) of Pakistan: a catalogue and faunistic review - Hassan, Muhammad Asghar; Oswald, John D.; Zia, Ahmed; Liu, Xingyue (Zootaxa, 2019)
The first comprehensive catalogue of the extant Neuropterida of Pakistan is presented, and the known distributions of all of these species from Pakistan are summarized. The fauna, as presently known, comprises 113 species in 63 genera and 11 families, but this certainly attributes to a significant under-representation of the true fauna. Eighteen species are presently known only from Pakistan and are possibly endemic. The biogeography and several related aspects of the fauna are discussed.